(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Focusing on clinical trials in the time of a pandemic, the contribution offers a comprehensive overview of the main challenges for investigators-physicians and patient-participants, discussing their ethical implications for the informed consent. Namely, adaptive and pragmatic trial designs can balance the rapidly changing standards of care with speed and agility, but these are designs which encompass specific implications for the informed consent process; the move towards the use of off-label drugs and compassionate pharmaceuticals in pandemics, which has been unavoidable due to the urgency of treating patients and the lack of knowledge on the virus, on the other hand raises many ethical questions that should be carefully addressed; the impact of the pandemic on ongoing clinical trials and on new trials, due to Covid-19 restrictions, needs proper consideration as well. Moreover, the contribution discusses the ethical conditions for deferred consent and key elements of re-consent alongside with ethical issues related to an electronic-digital consent in the case of tele-medicine and remote information-monitoring. Finally, the article encompasses a focus on patients’ vulnerabilities, including specific vulnerabilities (age, gender and ethnicity) that should be protected in conducting clinical research.